Combined versus sequential penetrating keratoplasty and cataract surgery for herpes simplex keratitis: a retrospective study - Wang, Yani; Cheng, Jun; Yang, Nannan; Li, Ting; Dong, Yanling; Xie, Lixin (Frontiers in Medicine, 2023)
Purpose: To compare the surgical outcomes of combined penetrating keratoplasty (PK) and cataract surgery with those of sequential surgery (cataract surgery after PK) for herpes simplex keratitis (HSK). Methods: The medical records of consecutive patients diagnosed with HSK who underwent combined or sequential PK and cataract surgery in active and stable stages between June 2015 and June 2022 were reviewed retrospectively. Complications, graft survival, endothelial cell density (ECD), and final BCVA were compared and analyzed between both surgical methods in each stage.Results: A total of 171 eyes of 171 patients were enrolled, including active stage (69 combined, 46 sequential) and stable stage (34 combined, 22 sequential). The average follow up was 24.2 ± 15.8 months (range, 3 months -48 months). The final BCVA had obvious improvement and the postoperative ECD was not different in combined and sequential groups of each stage. In sequential group of active stage, 66.7% of persistent epithelial defects and 50% of HSK recurrence occurred within 3 months after cataract surgery; Nevertheless, compared to that in sequential group, capsular rupture (P =0.021), persistent epithelial defects (P = 0.027), and HSK recurrence (P = 0.035) occurred more frequently in combined group, leading to a lower graft survival rate (P =0.045); at the last visit, 46.4% and 67.4% of grafts remained clear in combined and sequential groups, respectively. By contrary, 82.4% and 50.0% of grafts remained clear in stable stage of combined and sequential groups at the last visit, respectively, and a higher graft survival rate was observed in combined group (P = 0.030). Conclusion: Although the postoperative ECD is not different between two surgical groups in each stage, sequential surgery in active stage of HSK seems to have advantages in less complications and higher graft survival rate, whereas combined surgery in stable stage has a better outcome than that in sequential surgery.